Basic principles of thermo-acoustic energy and temporal profile detection of microwave pulses - Andreev, V.G.; Karabutov, A.A.; Vdovin, V.A. (Вопросы атомной науки и техники, 2001)
Basic principles of a thermo-acoustic method developed for the detection of powerful microwave pulses of nanosecond duration are discussed. A proposed method is based on the registration of acoustic pulse profile originated from the thermal expansion of the volume where microwave energy was absorbed. The amplitude of excited acoustic transient is proportional to absorbed microwave energy and its temporal profile resembles one of a microwave pulse when certain conditions are satisfied. The optimal regimes of microwave pulse energy detection and sensitivity of acoustic transient registration with piezo-transducer are discussed. It was demonstrated that profile of a microwave pulse could be detected with temporal resolution of 1 – 3 nanosecond.